Cerebral venous thrombosis in pregnant and postpartum women presenting to the emergency department with headaches - Aaron Jacob Grossberg; Sagar C Galwankar (Journal of Emergencies, Trauma and Shock, 2024)
Introduction: Cerebral venous thrombosis (CVT) is a thromboembolic disease of the intracranial venous systems. The disease can be difficult to diagnose as it often requires a high index of suspicion. Risk factors for the disease include pregnancy, oral contraceptive pills, congenital thrombophilia, infection, cancer, polycythemia, head trauma, and recent surgery. However, there have been no studies in the United States that have examined whether pregnancy and the postpartum stage are truly a risk factor for CVT. The aim of this study is to determine whether pregnant and postpartum women presenting to the emergency department with headaches have a higher incidence of CVT to better risk stratify which patients need to have advanced imaging pursued. Methods: A retrospective, observational case–control study was performing by querying the electronic medical record at a large county hospital for patients presenting with a headache to the emergency department. Patients were stratified into groups based on whether they were diagnosed with CVT, pregnancy status, and comorbid conditions to determine the risk associated between pregnancy, the puerperium stage, and CVT. Results: A total of 20,955 males and females presented to the emergency department between January 1, 2016 and April 13, 2023, with a chief complaint of headache. There were 19,474 female patients and 9581 male patients. In the case group, there were 793 pregnant women and 53 postpartum women. In the control group, there were 18,628 women who were not pregnant. Of the 22 patients diagnosed with CVT, 1 was in the puerperium stage and no patients were pregnant. Pregnant and postpartum patients were 1.05 (0.14–7.80) times more likely to develop CVT. Pregnant and postpartum patients were 1.73 (0.23–13.52) times more likely to develop CVT when controlled for comorbidities. Patients in the puerperium stage were 26.48 (3.33–210.87) times more likely to develop CVT when controlled for comorbidities. Conclusion: Pregnant patients presenting to the emergency department with headaches do not have a significantly higher risk of CVT; however, puerperium patients have a significantly higher risk of CVT compared to the general population.